Nilai-nilai Budaya dalam Pantun Melayu Patani dan Implikasinya dalam Pembelajaran Bahasa dan Sastra di Tsanawiyah Patani - Masoh, Aminoh (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
This thesis is to find out the value of culture in Patani Melayu poem the name of book ?Bunga Rampai Sastra Melayu Patani Lama? and it implication in language and literature learning at Tsanawiyah Patani. Method that used is describtive analysis method which be scribe about the object which analised through the data which have collected. And then the result of the research processed and analised to take the conclusion. The result of the research show that the poem book :?Bunga Rampai Sastra Melayu Patani Lama? includ many value of culture which must be example for the reader. The researcher can take te conclusion that the value of the culture in Patani Melayu poam examined base on six systems of cultures value which universal. There are technology system : productive tools which related to the work, weapon tools which be heirloom, and simple transportation. Economy system : job in agree culture, plantantion, commerce small company, islamic cooperation and fisherman. Social organization : Unity in family, unity out of family are unity in the society and nation, organization and structure of society. Knowledge system : knowledge about the nature around it, knowledge about substances and unripe matter and things in it environment, and the knowledge about characteristics and behavior in humanity. Art : building art which includ, art form which carved in the oldest mosque in Patani. Religion system : believe system, seremony of religion, and the mamber?s of religious community. Implication the result of this research is language and literature learning at Tsanawiyah in Patani by using book?s poem : ?Bunga Rampai Sastra Melayu Patani Lama? as a learning saurce which potinced to produce the students to love, to presave, and to imitate. From this character?s student there is hope to notion generation which good behavial to relize their identity which can bring the notion and religion to be better condition.